On the Use of a Retarding Field Energy Analyzer for Plasma Flow Analysis. Issue 1 (9th January 2013) - Fredriksen, Å.; Miloch, W. J.; Gulbrandsen, N.; Mishra, L. N.
Abstract Measurements of plasma flow are of key interest in a number of plasma environments and applications. In laboratory magnetized plasmas, the directional Langmuir or Mach probe is a well‐proven 'in‐situ' diagnostic tool to obtain the flow velocity. However, in non‐magnetized or weakly magnetized plasmas, this method does not readily yield reliable velocity measurements, as it has been shown by numerical and experimental studies that the collection of upstream ions to the rearward probe surface can be significant. In this study, we have utilized the analysis of data from 3D PIC simulations [W. J. Miloch, Plasma Phys. Contr. Fusion 52, 124004 (2010)] of ion velocity distributions in the vicinity of a negatively biased object embedded in a collision‐less, source‐free plasma with and without flow. The simulations allow us to study how the grounded probe housing of a retarding field ion energy analyzer (RFEA) affects the distribution of ions and their collection at different angles with flowing, electropositive plasma. We find that an analysis based on derived plasma potential at different angles with the flow, may provide more consistent results than the Mach probe theory in our weakly magnetized case. Comparisons are carried out with RFEA measurements in an inductively coupled helicon plasma (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)